2009
DOI: 10.1128/jvi.02393-08
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T-Cell-Mediated Heterologous Immunity between Mycobacteria and Poxviruses

Abstract: The bacillus Calmette-Guerin (BCG) strain of Mycobacterium bovis is used in many parts of the world as a vaccine against Mycobacterium tuberculosis. Some epidemiological evidence has suggested that BCG immunization may have unpredicted effects on resistance to other pathogens. We show here in a mouse model that BCG immunization followed by antibiotic treatment to clear the host of the pathogen rendered three strains of mice partially resistant to infection with vaccinia virus (VV) but not to lymphocytic chorio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 56 publications
(103 reference statements)
2
98
0
5
Order By: Relevance
“…There is unequivocal evidence from studies in animals that infections and vaccines alter the subsequent response to unrelated (heterologous) infections 16 21 44. Randomised trials suggest that measles vaccine reduces mortality from infections other than measles by 47% (95% CI 23% to 63%) in girls (table 1) and that BCG reduces mortality from diseases other than tuberculosis by 25% (95% CI 6% to 41%) in girls and boys combined (table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is unequivocal evidence from studies in animals that infections and vaccines alter the subsequent response to unrelated (heterologous) infections 16 21 44. Randomised trials suggest that measles vaccine reduces mortality from infections other than measles by 47% (95% CI 23% to 63%) in girls (table 1) and that BCG reduces mortality from diseases other than tuberculosis by 25% (95% CI 6% to 41%) in girls and boys combined (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies of the non-specific effects of BCG in animals,11 21 and some of the mechanisms are understood 44. In the 1940s and 1950s, several controlled trials were performed in children in the USA and the UK to evaluate the effect of BCG vaccination on mortality.…”
Section: Bacillus Calmette–guerin Vaccinementioning
confidence: 99%
“…It can lead to enhanced or diminished protective immunity and can alter immunopathology. In previous studies it was found, that infections with Bacillus Calmette-Guérin (BCG), IAV, LCMV, mouse cytomegalovirus and Pichinde virus all confer a level of protective immunity against vaccinia virus (Selin et al, 1998;Mathurin et al, 2009;Chen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…79,80 This is similar to results in adult mouse models of heterologous immunity where it was demonstrated that BCG-immune mice were more resistant to vaccinia virus infection and that this resistance was mediated by IFNg-producing CD4 T cells. 81 Interestingly, Steenhuis and others showed that in children, by 18 months of age, immunization with BCG resulted in lowered numbers of children with eczema, a Th2-immune mediated disease. 82 …”
Section: Measles Vaccinementioning
confidence: 99%